Verbal and nonverbal concomitants of rapport in health care encounters: implications for interpreters - Emilia Iglesias Fernandez (JoSTrans: The Journal of Specialised Translation)
This article examines verbal and nonverbal rapport in mediated healthcare encounters. A review of nine studies reveals the interpreters' tendency to editorialise non medical facts, repetitions, variation, emphasis and verbal and nonverbal back-channelling as they seem to regard this information as non medically relevant. Medical rapport, however, is mostly relayed through these verbal and nonverbal behaviours, and thus the development of doctor-patient involvement in the interaction can be compromised. Doctors' and interpreters' views on rapport are analysed, and implications for training and research are extracted.